2012
DOI: 10.1210/jc.2012-2444
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Occult Central Lymph Node Metastasis in Papillary Thyroid Carcinoma by Preoperative BRAF Analysis Using Fine-Needle Aspiration Biopsy: A Prospective Study

Abstract: Preoperative BRAF analysis by FNAB and primary tumor size based on ultrasonography may assist in predicting occult central lymph node metastasis in patients with PTC and clinically node-negative neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 45 publications
4
73
0
Order By: Relevance
“…LVI and CLNM showed a significant correlation in our study, similar to the result of Joo et al (34,35) but different from that of Roh et al (19). Considering the anatomical structure of thyroid gland and its well-developed lymphovascular structure that drains primarily to cervical lymph node (36), our result of a correlation between LVI and CLNM is logical.…”
Section: Discussionsupporting
confidence: 64%
“…LVI and CLNM showed a significant correlation in our study, similar to the result of Joo et al (34,35) but different from that of Roh et al (19). Considering the anatomical structure of thyroid gland and its well-developed lymphovascular structure that drains primarily to cervical lymph node (36), our result of a correlation between LVI and CLNM is logical.…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, it has been suggested that the identification of a possible unfavorable risk factor, such as the presence of BRAF mutation, before surgery would allow an aggressive initial approach, such as central LN dissection (28). We evaluated BRAF C patients submitted either to thyroidectomy or thyroidectomy plus prophylactic CND and found no difference in outcome, despite more frequent LNs metastasis in subjects submitted to TTCCND (PZ0.002).…”
Section: Clinical Study D L S Danilovic and Others Preoperative Molecmentioning
confidence: 91%
“…Although the BRAF gene mutation is associated with greater initial aggressiveness of papillary carcinoma, including higher frequency of lymph node metastases, the available data are not sufficient to rule out or indicate elective dissection of the central compartment lymph nodes on the grounds of the absence or presence of this mutation, respectively (84,85).…”
Section: Recommendation 32mentioning
confidence: 96%